Metachronous multifocal early gastric cancer after partial gastrectomy for synchronous multifocal early gastric cancer: a case report and literature review - Qiang Geng; Qing Yang; Shubei Chen; Wei Qiu; Xiaoling Liu; Changfeng Sun; Cunliang Deng; Ou Jiang (Frontiers in Medicine, 2026)
With the rapid advancement of digestive endoscopy techniques, an increasing number of early gastric cancers (EGCs) have been diagnosed and treated, substantially improving the 5-year survival rate of patients with EGC. Multifocal gastric cancer is a relatively uncommon subtype, and repeated occurrences of multifocal gastric cancer are even less frequently observed. The pathogenesis may involve persistent field cancerization of the background gastric mucosa and, in some patients, an inherited predisposition; evaluation of mismatch repair (MMR) status is an important component of the assessment. Here, we report a young male patient who experienced two episodes of multifocal early gastric cancer over a 9-year period. Both episodes were treated with curative intent—initially by proximal one-third gastrectomy for synchronous multifocal early gastric cancer and subsequently by minimally invasive endoscopic resection for metachronous multifocal early gastric cancer in the remnant stomach. This case suggests that patients with synchronous multifocal early gastric cancer remain at risk for metachronous multifocal gastric cancer even after curative treatment. In particular, among those with high-risk profiles—including a family history of cancer, Helicobacter pylori infection, and gastric mucosal atrophy with intestinal metaplasia—greater emphasis should be placed on high-quality endoscopic screening, long-term surveillance, and genetic susceptibility assessment when indicated.